PERANCANGAN SISTEM INFORMASI MANAJEMEN UNTUK PARIWISATA DI JAWA TIMUR PADA AGEN PERJALANAN - Yohana Tesalonika Kristanti; Indri Hapsari; Jerry Agus Arlianto (Perpustakaan Universitas Surabaya, 2018)
At this time, travel agents not only provided her services to consumers but they should also be able to answer the needs of just about any desired consumers. If the consumer's wishes are met then the satisfaction of such services will be increased. The problem is generally a tour package that is sold to consumers is a tour package that was already previously designed so that tourist attractions, hotels, dining already determined by a travel agent instead of the consumer (ready made). In addition the price of package tours have also been determined by a travel agent, so it is less varied and can not adjust the budget consumer. The last issue is from a travel agent as a service that caters to consumers during a journey does not yet have a database about the information needs of tourism in East Java as well as systems that can make it easier to travel agencies to design packages tourism in East Java which can adapt to the desires of consumers. In this research will be designed the database and information system for tourism in East Java which can help travel agents in designing tourism packages. The objectives to be achieved in this research is to design a system of information on tourism in East Java to make it easier for travel agencies in designing tourism packages that suit both desire the desire of tourist attractions, hotels, places of meals, transportation, as well as the desired budget travelers. The steps in making a database from the information already collected into the database server in this study using a Microsoft Access database server 2013. The result of processing the database to display the table, query, form, and report to make it easier to find and manipulate information about the needs of tourism in East Java. Then perform system validation information to know if the information system is already well underway as desired.On the validation test results show the same value between the calculation of the manual with the calculation system, so it can be said the system already made is valid and can be used for the needs of travel agents. The existence of information systems, travel agents do not need a long time to search the desired tourism needs of consumers that is approximately 15 minutes, 30 minutes faster than using manual systems because all the data is already There are in the database, live match data which is in accordance with the wishes of the consumer. Time in putting together a package tour and doing the calculations did not take a long time that is approximately 5 minutes 40 seconds faster than using a manual system because the calculations are already automatically after the user entered data. The use of these information systems provide ease of travel agencies in conducting operational activities as well as security, service, efficiency can be increased.